Role of the adaptive immune system in diabetic kidney disease - Kong, Lingyun; Andrikopoulos, Sofianos; MacIsaac, Richard J; Mackay, Laura K; Nikolic‐Paterson, David J; Torkamani, Niloufar; Zafari, Neda; Marin, Evelyn C S; Ekinci, Elif I (Journal of diabetes investigation, 2022)
Diabetic kidney disease (DKD) is a highly prevalent complication of diabetes and the leading cause of end‐stage kidney disease. Inflammation is recognized as an important driver of progression of DKD. Activation of the immune response promotes a pro‐inflammatory milieu and subsequently renal fibrosis, and a progressive loss of renal function. Although the role of the innate immune system in diabetic renal disease has been well characterized, the potential contribution of the adaptive immune system remains poorly defined. Emerging evidence in experimental models of DKD indicates an increase in the number of T cells in the circulation and in the kidney cortex, that in turn triggers secretion of inflammatory mediators such as interferon‐γ and tumor necrosis factor‐α, and activation of cells in innate immune response. In human studies, the number of T cells residing in the interstitial region of the kidney correlates with the degree of albuminuria in people with type 2 diabetes. Here, we review the role of the adaptive immune system, and associated cytokines, in the development of DKD. Furthermore, the potential therapeutic benefits of targeting the adaptive immune system as a means of preventing the progression of DKD are discussed. Although the role of the innate immune system in diabetic renal disease has been well characterized, the potential contribution of the adaptive immune system remains poorly defined. Here, we review the role of the T and B cells of the adaptive immune system, and associated cytokines, in the development of diabetic kidney disease.